The Case for Live Attenuated Vaccines against the Neglected Zoonotic Diseases Brucellosis and Bovine Tuberculosis. - Aseem Pandey; Ana Cabello; Lavoisier Akoolo; Allison Rice-Ficht; Angela Arenas-Gamboa; David McMurray; Thomas A Ficht; Paul de Figueiredo (Public Library of Science (PLoS), 2016)
Vaccination of humans and animals with live attenuated organisms has proven to be an effective means of combatting some important infectious diseases. In fact, the 20th century witnessed tremendous improvements in human and animal health worldwide as a consequence of large-scale vaccination programs with live attenuated vaccines (LAVs). Here, we use the neglected zoonotic diseases brucellosis and bovine tuberculosis (BTb) caused by Brucella spp. and Mycobacterium bovis (M. bovis), respectively, as comparative models to outline the merits of LAV platforms with emphasis on molecular strategies that have been pursued to generate LAVs with enhanced vaccine safety and efficacy profiles. Finally, we discuss the prospects of LAV platforms in the fight against brucellosis and BTb and outline new avenues for future research towards developing effective vaccines using LAV platforms.